Latin America and the European Union: Conceptual Approaches and Practice of Economic Cooperation - Violetta M. Tayar (Vestnik RUDN. International Relations, 2022)
The article deals with North - South cooperation between the European Union (EU) and Latin America and the Caribbean (LAC) with an emphasis on bilateral trade. Over the past decades, cooperation with the EU has been perceived in LAC as a counterweight to the US dominance and one of the priorities of external economic relations. The article presents a retrospective of theoretical approaches of the non-Western Latin American school of UN Economic Commission for Latin America and the Caribbean (ECLAC, CEPAL in Spanish) to the economic cooperation with the EU. A feature of the article is the study of trade interaction between the LCA and the EU countries. When analyzing the dynamics of trade during the first two decades of the 21st century the author of the article comes to the conclusion that the trade exchange between the EU and the LCA is uneven. There are many LAC countries that continue to export low-value-added products to the EU. Thus, the dichotomy between two models of commercial specialization of LAC has exacerbated. On one hand, there is a model of South American countries focused on raw materials (MERCOSUR, Andean Community), and, on the other hand, there is a model that includes the export of manufactured products and participation in industrial production chains (Mexico, Central America). The article concludes that MERCOSUR will probably face a number of trade challenges related to its model of economic globalization, particularly with regard to its export specialization in commodities and food. The relevance of the study is due to the fact that in the context of exacerbation of geopolitical contradictions and a changing world order, it is important to analyze the Latin American approach to economic cooperation with the EU countries, among which, in turn, there is a growing understanding that still free niches in the Latin American market can be occupied by China or other partners not belonging to the collective West.